Strategy For Fulfilling Raw Materials Cassava (Manihot Esculenta) In The Cassava Chips Industry, Rancabungur District, Bogor Regency - Agustia Rizka Ananda; Himmatul Miftah; Siti Masithoh (JURNAL AGRIBISAINS, 2026)
The cassava chips industry is one of the developing agricultural processing industries in Rancabungur District which plays an important role in the local economy. This research was motivated by the existence of obstacles in fulfilling the supply of cassava by several cassava chips industries in Rancabungur District. The aim of this research is to analyze strategies for fulfilling cassava in the cassava chips industry. The analytical method used is descriptive analysis which includes analysis of performance indicator inefficiencies as well as source and quantitative mapping analysis. The results of the research show that the performance indicators that require improvement are 13 of the 23 performance indicators. Cassava fulfillment strategies that can be formulated based on the results of the analysis are 6 strategies for improving the upstream supply chain and 7 strategies for improving the industrial supply chain system. The main strategies that can be focused more on fulfilling cassava raw materials include 2 strategies for improving the upstream supply chain and 5 strategies for improving the industrial supply chain system.